Pengaruh Literasi Digital, Efikasi Diri dan Lingkungan Terhadap Intensi Berwirausaha E-Business Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret - Khoiriyah, Ririn; Sudarno, Sudarno; Setyowibowo, Feri (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This study aims to determine the effect of digital literacy variabels, own variabels and environmental variabels on the variabels in the e-business entrepreneurship carried out by students of Economic Education at the University of March. This research is quantitative or the data collection is carried out through questionnaires distributed to the respondents. Economic Education students at Sebelas Maret University Class of 2017-2019 are 241 students as a research population. The number of samples in this study was 151 students and the sampling technique used by the researchers was proportional stratified random sampling. Multiple linear regression tests became the investigator's chosen data analysis. The results of the study found that: (1) the variabel digital literacy influences the variabel intensity of entrepreneurship in electronic commerce. (2) the self-efficacy variabel influences the intensity variabel of entrepreneurship in e-business. (3) environmental variabels influence the intensity of e-business entrepreneurship variabels.